literature review Penggunaan Teknologi Telenursing Pada Klien Skizofrenia Dalam Pelayanan Keperawatan Jiwa - Yunita Anggraini (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Across the world, schizophrenia affects about one billion people. Schizophrenia is a mental disorder that can affect the way persons thinks and expresses emotions. Most patients who suffering schizophrenia is at very high risk of relaps. As technology develops, Telenursing can be used to provide care provision and patient monitoring, encouraging active thinking between patients and family members. Objective: to describing the application of telenursing in clients with schizophrenia. The author uses literature reviews which are summaries of 10 article on several search databases, namely Google Scholar, Scopus, Science Direct, and Elsevier. Based on the literature review that the authors review of 10 articles found that telenursing could prove time efficiency in long distance service and improve client medication adherence. Telenursing provides many benefits for clients and families, one of which is prove long distance services and cost limitations